Intracranial Efficacy of Pyrotinib and Capecitabine Combination Therapy in HER2-Positive Breast Cancer with Brain Metastases - Wang C; Xiang J; Zhang Q; Li J; Liu Y; Liu J (Drug Design, Development and Therapy, 2024)
Congcong Wang,1,* Jinyu Xiang,1,* Qingyu Zhang,1 Jing Li,1 Yanqing Liu,2 Jiannan Liu1 1Department of Oncology, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai, Shangdong, 264000, People’s Republic of China; 2Department Brest Surgery, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai, Shangdong, 264000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiannan Liu, Department of Oncology, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, No. 20 Yuhuangding East Road, Yantai, 264000, People’s Republic of China, Email ljnwcc@163.com Yanqing Liu, Department Brest Surgery, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, No. 20 Yuhuangding East Road, Yantai, 264000, People’s Republic of China, Email liuyanqing927@163.comAim: Approximately 50% of patients diagnosed with human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (BC) are estimated to develop brain metastases (BMs). This study was aimed to assess the intracranial efficacy and survival benefits of pyrotinib and capecitabine combination therapy in the treatment of BMs in patients with HER2-positive BC.Methods: A total of 56 HER2-positive BC patients with BMs were treated with 400 mg pyrotinib once daily along with 1000 mg/m2 capecitabine twice daily for 14 days in 21-day cycles. The patients were allocated into three cohorts: (1) Cohort A composed of patients with newly diagnosed BMs without prior local radiotherapy, (2) Cohort B included patients with stable post-local radiotherapy, and (3) Cohort C composed of patients with progression following local radiotherapy. The primary endpoint was the intracranial objective response rate (CNS-ORR), while secondary endpoints included intracranial disease control rate (CNS-DCR), progression-free survival (PFS), overall survival (OS), safety, as well as QoL.Results: The observed CNS-ORR CNS-ORR of 72.73% (95% CI 51.85– 86.85%) in cohort A, 55% (95% CI 34.21– 74.18%) in cohort B, and 42.86% (95% CI 21.38– 67.41%) in cohort C. The mPFS was 11 months, 8.4 months, and 5.2 months in cohorts A, B, and C, respectively. Diarrhea, accounting for 23.21% of all the patients, was the most common grade 3/4 adverse event related with treatments (6/22 [27.3%] in cohort A, 4/20 [20.0%] in cohort B, and 3/14 [21.4%] in cohort C). However, there were no deaths related with treatments observed. Importantly, the QoL was efficiently maintained throughout the treatment duration.Conclusion: Pyrotinib and capecitabine combination therapy proved significant effectiveness as well as tolerability in treating HER2-positive BC with BMs, yielding satisfactory results, especially in radiotherapy-naive population.Keywords: breast cancer, brain metastases, pyrotinib, capecitabine, HER2, radiotherapy